Construction of Molybdenum Disulfide/Biological Structure Carbon Composite Photocatalysts and Their Photocatalytic Hydrogen Production - Wang, Shujing; Ding, Jiajing; Wang, Chencheng; Li, Wanfei; Chen, Zhigang; Liu, Chengbao; Chen, Feng (Frontiers in Materials, 2022)
The hydrothermal calcination method using bamboo leaves as the biological template, thiourea as the sulfur source, and molybdenum chloride as the molybdenum source was employed to synthesize the molybdenum disulfide/biological structure carbon (MoS2/C) photocatalytic composites with different concentrations of molybdenum chloride. The thermal decomposition behavior, surface morphology, phase structure, BET specific surface area, optical and photoluminescence properties, and photocatalytic activity of MoS2/C photocatalytic composites with different concentrations of molybdenum chloride were studied. The results showed that the optimal temperature for synthesizing MoS2/C photocatalytic composites is 700°C. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) observations show that the hydrothermal calcination method can be used to load MoS2 onto the biological carbon and form a structurally stable composite system. Analysis of optical and photoluminescence properties shows that the MoS2/C composites prepared by the hydrothermal calcination method with the concentration of molybdenum chloride of 0.20 mol/L exhibit a high charge transfer and separation efficiency. Photocatalytic experiments show that the MoS2/C composites prepared by the hydrothermal calcination method with the concentration of molybdenum chloride of 0.20 mol/L have a high photocatalytic activity and cyclic stability. This excellent synthesis strategy can be used to synthesize other photocatalytic hydrogen production materials.